2008
DOI: 10.1136/bmj.39430.529549.be
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin “resistance” and risk of cardiovascular morbidity: systematic review and meta-analysis

Abstract: Objective To determine if there is a relation between aspirin "resistance" and clinical outcomes in patients with cardiovascular disease. Design Systematic review and meta-analysis. Data source Electronic literature search without language restrictions of four databases and hand search of bibliographies for other relevant articles. Review methods Inclusion criteria included a test for platelet responsiveness and clinical outcomes. Aspirin resistance was assessed, using a variety of platelet function assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
526
3
24

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(582 citation statements)
references
References 25 publications
21
526
3
24
Order By: Relevance
“…13 In a recent meta-analysis of 20 studies investigating aspirin resistance, a total of 6 different platelet function assays were used, including studies reflecting both in vivo and ex vivo platelet activity. 14 Commonly used platelet function assays, including their strength and limitations, are summarized below (Table 1).…”
Section: Diagnostic Testing Of Platelet Functionmentioning
confidence: 99%
“…13 In a recent meta-analysis of 20 studies investigating aspirin resistance, a total of 6 different platelet function assays were used, including studies reflecting both in vivo and ex vivo platelet activity. 14 Commonly used platelet function assays, including their strength and limitations, are summarized below (Table 1).…”
Section: Diagnostic Testing Of Platelet Functionmentioning
confidence: 99%
“…The latter is a stable metabolite excreted in urine, and its measurement provides a reliable estimate of the total in vivo production of TXA 2 including the extraplatelet sources 7, 8. 11‐Dehydro‐TXB 2 has been found to be elevated in several atherothrombotic diseases and to correlate with major adverse clinical events 9, 10, 11, 12, 13, 14. However, none of the studies have evaluated the association of 11‐dehydro‐TXB 2 with patients’ long‐term outcomes in AMI.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that this antibody does not interfere with physiological hemostasis 19. Aspirin remains the only clinically approved agent for therapeutic interventions that target this pathway, but its use is associated with many limitations, including severe adverse effects (eg, bleeding) and resistance, among others 25, 26, 28, 29, 58. Based on these considerations, there remains interest in developing more selective and new/novel means for targeting the TXA 2 /TPR pathway (namely, agents with TPR antagonistic activity, because they would be expected to exhibit a better/safer pharmacological profile and perhaps be more effective in managing thrombosis‐based diseases).…”
Section: Discussionmentioning
confidence: 77%